Stories Stories of Prevailing: Novice Teachers’ Journey in Far-flung Schools in the Time of COVID-19 Pandemic - Hipolito, Mark Floricar G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This study was conducted to explore the experiences of novice teachers assigned in far-flung schools during the COVID-19 pandemic, anchoring on reflective practice guided by David Kolb's experiential learning theory. As a strategy to understand the experiences of novice teachers, the researcher employed mini-virtual ethnography by interviewing four novice elementary teachers teaching in schools located in mountainous areas through phone calls and messenger chat. The data gathered were analyzed using thematic analysis. Recorded interviews were transcribed, coded, and sorted to identify the different themes. The study revealed that teachers experienced challenging and fulfilling encounters on their journey. To cope with the challenges brought by the pandemic, the teachers find means to ensure that education continues amidst the crisis with the help of various stakeholders. Out of their experiences, teachers have gained a lot of realizations and aspirations for their students, parents, and self. They've seen that what they went through will help them become stronger, and there is still hope despite what is happening. By engaging in reflective practice, using Kolb's learning cycle, teachers could think and reflect on their experiences, learn from the experience, plan for a change, and improve their learning and instructional practices